Method for improving electric conductivity of C17460 beryllium copper
By introducing zirconium elements into C17460 beryllium copper and performing multiple refining and heat treatments, the technical bottleneck of improving the conductivity of C17460 beryllium copper in the prior art has been solved, and the conductivity is significantly improved on the basis of maintaining strength, hardness and high temperature resistance. rate effect.
Patent Information
- Application Number
- CN202411576897.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-21
AI Technical Summary
The prior art is difficult to significantly improve its conductivity while maintaining the strength, hardness and high-temperature softening properties of C17460 beryllium copper, and its production cost and difficulty are relatively high.
By laying electrolytic copper, nickel and zirconium in a specific order in a vacuum smelting furnace, and performing multiple refining and casting, a copper-nickel zirconium alloy is obtained, and then smelted with the beryllium copper master alloy while feeding to form a C17460 beryllium copper casting ingot . Subsequently, a stepper furnace is used for hot rolling and solid solution treatment, further improving the conductivity.
On the basis of maintaining the original excellent mechanical properties of C17460 beryllium copper, it significantly improves its conductivity, reduces production difficulty and cost, and is suitable for applications in high-tech fields.
Smart Images

Figure BDA0005122006760000151 
Figure BDA0005122006760000161
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of beryllium copper alloy processing, and in particular relates to a method for improving the electrical conductivity of C17460 beryllium copper. Background Art
[0002] As a high-performance copper alloy, C17460 beryllium copper has shown broad application prospects in many high-tech fields such as aerospace, electrical and electronic, and chemical engineering due to its excellent corrosion resistance, high strength, high hardness, and good electrical conductivity. In these fields, electrical conductivity, as an important indicator for measuring material performance, directly affects the material's performance and application range. However, despite the many advantages of C17460 alloy, further improvement of its electrical conductivity on the basis of ensuring strength and hardness faces technical bottlenecks.
[0003] At present, the methods for improving the conductivity of metal materials mainly focus on adding trace elements to refine the grains or change the chemical composition. For C17460 alloy, although these methods have improved the conductivity to a certain extent, there are still significant limitations. Specifically, although the trace element addition method can refine the grains, its effect is limited and the uniformity of the ingot composition is extremely high, which increases the production cost and difficulty; while changing the chemical composition may improve the conductivity, it may be at the expense of the strength, hardness or formability of the material. Therefore, how to significantly improve the conductivity of the C17460 alloy while maintaining its original excellent mechanical properties has become a technical problem that needs to be solved urgently. Summary of the invention
[0004] The object of the present invention is to provide a method for improving the electrical conductivity of C17460 beryllium copper, which can improve the electrical conductivity of C17460 beryllium copper while maintaining the original excellent mechanical properties (such as strength, hardness and high temperature softening resistance) of C17460 beryllium copper, and has low production difficulty and low cost.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for improving the conductivity of C17460 beryllium copper, the method comprising:
[0007] Step S1, in the order of electrolytic copper, nickel, electrolytic copper, zirconium and electrolytic copper, electrolytic copper, nickel and zirconium are laid from bottom to top in a vacuum melting furnace, vacuum melting for 10 to 15 minutes at a vacuum degree of 0.074 to 0.094 MPa and a temperature of 1460 to 1530° C., and then refined for 28 to 38 minutes at a temperature of 1460 to 1530° C., and then the refined alloy liquid is cast into a tundish, and then the alloy liquid surface in the tundish is covered with wood ash, and finally cast into a graphite mold and solidified to obtain a copper-nickel-zirconium alloy;
[0008] In the step S1, the mass ratio of the electrolytic copper, nickel and zirconium is 17-18:1-2:1;
[0009] Step S2, according to the order of electrolytic copper, copper-nickel-zirconium alloy, beryllium-copper master alloy and nickel, the electrolytic copper, copper-nickel-zirconium alloy, beryllium-copper master alloy and nickel are placed in a non-vacuum melting furnace for melting by adding materials and melting at the same time, and then cast and cool in sequence to obtain C17460 beryllium-copper ingot;
[0010] In the step S2, the mass ratio of the electrolytic copper, the copper-nickel-zirconium alloy, the beryllium-copper master alloy and nickel is 100-110:8-10:14-15:1;
[0011] Step S3, using a walking beam furnace to heat the C17460 ingot to 900-930° C., keeping the temperature for 8-14 hours, and then performing hot rolling, double-sided milling and rough rolling in sequence to obtain a C17460 strip with a thickness of 1.2-1.7 mm;
[0012] Step S4, after trimming and cleaning and brushing the C17460 strip in sequence, a solid solution treatment is performed in a hydrogen atmosphere at a temperature of 930 to 970° C. at a speed of 3 to 7 m / min;
[0013] Step S5, after the C17460 strip after the first solution heat treatment is subjected to second cleaning and brushing and first finish rolling in sequence, a second solution treatment is performed in a hydrogen atmosphere at a temperature of 930 to 970° C. at a speed of 8 to 13 m / min;
[0014] Step S6, sequentially performing three cleaning and brushing, two finishing rolling, one cleaning and one straightening on the C17460 strip after the secondary solution heat treatment;
[0015] Step S7, in a hydrogen atmosphere, heat the C17460 strip after drawing and straightening to 370-390°C at a heating rate of 110-130°C, and then age it for 2.5-3.5 hours; then heat it to 410-440°C, age it for another 2.5-3.5 hours, and then naturally cool it to 40°C before taking it out of the furnace; then perform secondary cleaning, secondary drawing and straightening, and slitting in sequence.
[0016] Further, in the step S1, the mass of each layer of electrolytic copper laid in the order of electrolytic copper, nickel, electrolytic copper, zirconium and electrolytic copper is the same;
[0017] In the step S1, the solidification temperature is 1070-1130° C. and the solidification time is 32-48 minutes.
[0018] Further, in the step S2, the beryllium content in the beryllium copper master alloy is 3.2-3.8%, and the rest is copper;
[0019] In step S2, the smelting temperature is 1260-1290°C and the time is 2-3h;
[0020] In step S2, the casting temperature is 1250-1290°C, the speed is 40-50 mm / min; the cooling medium is water at 28-35°C, and the water circulation speed is 1.6-1.9 m / min. 3 / h.
[0021] Furthermore, in the step S3, the hot rolling has 8 to 10 passes, the start rolling temperature is 870 to 890° C., the hot rolling time is 10 to 13 minutes, and the final rolling temperature is 660 to 680° C.;
[0022] In step S3, the double-sided milling is: milling 0.6-0.8 mm thick material from the upper surface and the lower surface of the hot-rolled coil obtained after the first hot rolling, and milling 4-6 mm wide material from the two sides of the hot-rolled coil;
[0023] In the step S3, the rough rolling is performed in 8 to 10 passes, the rolling force is controlled to be 280 to 450 tons, and the bending roll force is controlled to be 10 to 30 tons.
[0024] Furthermore, in the step S5, the number of rolling passes of the primary finishing rolling is 3 to 5, the rolling force is controlled to be 110 to 170 tons, and the bending roll force is controlled to be 12 to 70 tons.
[0025] Furthermore, in the step S6, the secondary finishing rolling has 2 to 3 passes, the rolling force is controlled to be 100 to 150 tons, and the bending roll force is controlled to be 15 to 60 tons;
[0026] In step S6, the elongation of the first straightening is 0.1-0.2%, and the inlet tension is 4-5 kg / mm 2 , the tension on the outlet side is 1.8~2.5kg / mm 2 .
[0027] Furthermore, in step S6, the cleaning process includes:
[0028] First use 1-2% degreasing agent for cleaning, then use 15-35% acid solution for cleaning, and finally use 0.1-0.3% passivation solution for cleaning;
[0029] In step S7, the secondary cleaning process includes:
[0030] First, use 1-2% degreasing agent for cleaning, then use 15-35% acid solution for cleaning; then use 580-620 mesh non-woven cloth for brushing; finally use 0.1-0.3% passivation solution for cleaning.
[0031] Further, the degreasing agent is K616 or DC-362 degreasing agent;
[0032] The acid solution is sulfuric acid or nitric acid;
[0033] The passivation solution is benzotriazole BTA or JCDH-2.
[0034] Furthermore, in step S7, the elongation of the secondary straightening is 0.1-0.2%, and the inlet tension is 4-5 kg / mm 2 , the tension on the outlet side is 2~3.5kg / mm 2 .
[0035] In summary, the technical solution of the present invention has the following technical effects:
[0036] The invention improves the conductivity of C17460 beryllium copper without reducing the strength, hardness and high temperature softening resistance of C17460 beryllium copper by adding zirconium element; the invention further ensures that the conductivity of C17460 beryllium copper is improved without reducing the strength and hardness of the C17460 beryllium copper material through graded aging treatment (i.e., two aging treatments), thereby solving the problem that the preparation process of the conductivity of C17460 beryllium copper in the prior art cannot achieve the best match between strength, hardness and conductivity; the invention does not need to add trace elements, does not have high requirements on the uniformity of the components of the C17460 beryllium copper ingot, and reduces the difficulty and cost of the production of C17460 beryllium copper; the Vickers hardness of the C17460 beryllium copper of the invention is 240-270 kgf / mm 2 , tensile strength is 790-880MPa, yield strength is 720-770MPa, elongation A50 is 10-13.8%, and conductivity is 52-58% IACS; the conductivity of C17460 beryllium copper of the present invention meets the requirements of high conductivity, is suitable for high-tech fields such as electronics, electricity, and communications, and has important application value. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] This embodiment provides a method for improving the conductivity of C17460 beryllium copper, the method comprising:
[0039] Step S1, in the order of electrolytic copper, nickel, electrolytic copper, zirconium and electrolytic copper, electrolytic copper, nickel and zirconium are laid from bottom to top in a vacuum melting furnace, vacuum melting for 10 to 15 minutes at a vacuum degree of 0.074 to 0.094 MPa and a temperature of 1460 to 1530° C., and then refined for 28 to 38 minutes at a temperature of 1460 to 1530° C., and then the refined alloy liquid is cast into a tundish, and then the alloy liquid surface in the tundish is covered with wood ash, and finally cast into a graphite mold and solidified to obtain a copper-nickel-zirconium alloy.
[0040] In order to ensure that the Zr element can be efficiently and evenly integrated into the matrix copper, this embodiment adopts vacuum melting technology. The mass ratio of electrolytic copper, nickel and zirconium in this embodiment is 17-18:1-2:1, which promotes the mutual solubility of zirconium Zr and Cu. The raw materials are placed in layers in the order of electrolytic copper-nickel-electrolytic copper-zirconium-electrolytic copper, and the mass of each layer of electrolytic copper after laying (i.e., layered placement) is the same, aiming to optimize the element distribution and reaction efficiency during the smelting process.
[0041] In order to prevent oxidation and ensure the stability of the alloy composition, the present embodiment uses plant ash to cover the entire alloy liquid surface. The solidification temperature in the present embodiment is 1070-1130° C. and the solidification time is 32-48 minutes.
[0042] Step S2, in the order of electrolytic copper, copper-nickel-zirconium alloy, beryllium-copper master alloy and nickel, the electrolytic copper, copper-nickel-zirconium alloy, beryllium-copper master alloy and nickel are placed in a non-vacuum melting furnace for melting by adding materials and melting at the same time, and then cast and cool in sequence to obtain a C17460 beryllium-copper ingot.
[0043] The mass ratio of electrolytic copper, copper-nickel-zirconium alloy, beryllium-copper master alloy and nickel in this embodiment is 100-110:8-10:14-15:1. The beryllium content in the beryllium-copper master alloy is 3.2-3.8%, and the rest is copper.
[0044] The smelting in this embodiment is non-vacuum smelting, the smelting temperature is 1260-1290°C, the time is 2-3 hours. The casting temperature is 1250-1290°C, the speed is 40-50 mm / min. The cooling medium is 28-35°C water, and the water circulation speed is 1.6-1.9 m / min. 3 / h. The cooling frequency is 2 to 3 times.
[0045] Step S3, using a walking beam furnace to heat the C17460 ingot to 900-930°C, keeping it warm for 8-14 hours, and then performing hot rolling, double-sided milling and rough rolling in sequence to obtain a C17460 strip with a thickness of 1.2-1.7 mm.
[0046] In this embodiment, the hot rolling has 8 to 10 passes, the start rolling temperature is 870 to 890° C., the hot rolling time is 10 to 13 minutes, the final rolling temperature is 660 to 680° C., and the C17460 ingot is gradually rolled from the initial specifications (such as 420*210mm) into a hot-rolled coil.
[0047] The double-sided milling in this embodiment is: 0.6-0.8 mm thick material is milled from the upper and lower surfaces of the hot-rolled coil obtained after one hot rolling, and 4-6 mm wide material is milled from the two sides of the hot-rolled coil, and finally the hot-rolled coil is milled to size.
[0048] The rough rolling in this embodiment has 8 to 10 passes, the rolling force is controlled to be 280 to 450 tons, the bending roll force is controlled to be 10 to 30 tons, and the hot rolled coil is further processed into strip (such as strip of about 1.5 mm).
[0049] Step S4, after trimming and cleaning and brushing the C17460 strip in sequence, a solid solution treatment is performed in a hydrogen atmosphere at a temperature of 930 to 970° C. at a speed of 3 to 7 m / min;
[0050] In this embodiment, a trimming machine is used to perform trimming on both sides (eg, 5 mm on each side) to remove defects such as cracks and burrs that may exist on the edge of the strip.
[0051] This embodiment uses a 500-mesh diamond brush roller + a 600-mesh alumina brush or a nylon brush roller to clean and brush the surface of the material once to remove surface residues and defects.
[0052] This embodiment uses a high hydrogen atmosphere for solid solution treatment to ensure uniform dissolution of alloy elements and optimize the microstructure of the material.
[0053] Step S5, after the C17460 strip has undergone the primary solution heat treatment, it is subjected to secondary cleaning and brushing and primary finish rolling in sequence, and then subjected to secondary solution treatment in a hydrogen atmosphere at a temperature of 930 to 970° C. and a speed of 8 to 13 m / min.
[0054] This embodiment again uses the brush roller combination of the same configuration (500 mesh diamond + 600 mesh alumina / nylon brush) to thoroughly remove the surface oxide layer produced by the initial solution treatment (i.e., the first solution treatment) and improve the appearance quality of the material.
[0055] In this embodiment, the number of rolling passes for a finishing rolling is 3 to 5, the rolling force is controlled to be 110 to 170 tons, and the bending roll force is controlled to be 12 to 70 tons. The strip is further processed to an intermediate thickness, the grains are further refined, and the strength and toughness of the strip are improved.
[0056] This embodiment further consolidates the effect of the initial solution treatment and improves the comprehensive performance of the material through secondary solution treatment.
[0057] Step S6, the C17460 strip after the secondary solution heat treatment is sequentially subjected to three cleaning and brushing operations, two finishing rolling operations, one cleaning operation and one straightening operation.
[0058] This embodiment repeatedly uses a high-efficiency brush roller combination to perform three cleaning and brushing operations to ensure that the surface oxide layer produced after the secondary solid solution is completely removed and the cleanliness of the strip surface is maintained.
[0059] The secondary finishing rolling of this embodiment has 2 to 3 rolling passes, the rolling force is controlled to be 100 to 150 tons, the bending roll force is controlled to be 15 to 60 tons, and the C17460 strip is rolled to the final specification size to meet the final size requirements.
[0060] This embodiment completely removes oil and residues on the surface of the strip through one cleaning, protecting the material from corrosion. The one-time cleaning process includes:
[0061] First, use 1-2% degreasing agent for cleaning, then use 15-35% acid solution for cleaning, and finally use 0.1-0.3% passivation solution for cleaning. Among them, the degreasing agent is K616 or DC-362 degreasing agent, the acid solution is sulfuric acid or nitric acid, and the passivation solution is benzotriazole BTA or JCDH-2.
[0062] This embodiment uses a single-stretching straightening method to accurately control the elongation of the stretching roller and the multi-roller straightening machine, perform plate straightening on the strip, improve its straightness, and release internal stress. The elongation of the single-stretching straightening in this embodiment is 0.1-0.2%, and the inlet tension is 4-5kg / mm 2 , the tension on the outlet side is 1.8~2.5kg / mm 2 .
[0063] Step S7, in a hydrogen atmosphere, heat the C17460 strip after drawing and straightening to 370-390°C at a heating rate of 110-130°C, and then age it for 2.5-3.5 hours; then heat it to 410-440°C, age it for another 2.5-3.5 hours, and then naturally cool it to 40°C before taking it out of the furnace; then perform secondary cleaning, secondary drawing and straightening, and slitting in sequence.
[0064] This embodiment uses graded aging (i.e., secondary aging treatment, pre-aging and final aging) to regulate the formation and distribution of precipitated phases, and significantly improve the electrical conductivity of the material while ensuring that the strength and hardness are not reduced.
[0065] The secondary cleaning process of this embodiment includes:
[0066] First, use 1-2% degreasing agent to clean and remove surface oil; then use 15-35% acid solution to clean and remove the oxide layer; then use 580-620 mesh non-woven cloth to gently brush and polish to ensure that the surface of the strip is as smooth as new and completely eliminate any minor defects; finally, use 0.1-0.3% passivation solution to clean and protect the material surface from corrosion. The degreasing agent is K616 or DC-362 degreasing agent, the acid solution is sulfuric acid or nitric acid, and the passivation solution is benzotriazole BTA or JCDH-2.
[0067] This embodiment uses secondary straightening to correct the minor deformation that may be caused by aging treatment, restore and optimize the flatness of the strip, and ensure that the product meets the highest quality standards. The elongation of the secondary straightening is 0.1-0.2%, and the inlet tension is 4-5kg / mm 2 , the tension on the outlet side is 2~3.5kg / mm 2 .
[0068] In this embodiment, the strip is slit according to the specified width specification and coil weight limit to meet customer requirements.
[0069] Embodiment 1:
[0070] Step S1, in the order of electrolytic copper-nickel-electrolytic copper-zirconium-electrolytic copper, the layers are placed in a vacuum melting furnace from bottom to top, the mass ratio of electrolytic copper, nickel and zirconium is 17:2:1, and the vacuum degree of 0.084Mpa and the temperature of 1500℃ are kept for a short time for 12min, and then refined for 30min at a temperature of 1500℃, and finally the slag is cleared and cast. The casting process is cast through the tundish, and the straw ash is immediately covered after the transfer, and the entire liquid surface must be fully covered. Finally, after casting in a graphite mold, it is solidified at a temperature of 1100℃ for 40min to obtain a copper-nickel-zirconium alloy. Among them, the mass of each layer of electrolytic copper is the same.
[0071] Step S2, according to the mass ratio of 105:9:14:1, in the order of electrolytic copper, copper-nickel-zirconium alloy, beryllium-copper master alloy and nickel, the electrolytic copper, copper-nickel-zirconium alloy, beryllium-copper master alloy and nickel are placed in a non-vacuum melting furnace by a method of adding materials and melting at the temperature of 1280°C for 2.5 hours, and then cast at the temperature of 1280°C at a speed of 45mm / min, and finally, 30°C water is used to heat the furnace at a speed of 1.8m 3 / h, and water circulation cooling is carried out to obtain C17460 beryllium copper ingot.
[0072] Step S3: Using a step-by-step furnace charging method, the C17460 ingot is heated to 910° C. After being kept warm for 12 hours, hot rolling, double-sided milling and rough rolling are performed in sequence to obtain a C17460 strip with a thickness of 1.5 mm.
[0073] Among them, the rolling passes of the first hot rolling are 9 passes, the starting rolling temperature is 880°C, the hot rolling time is 12 minutes, the final rolling temperature is 670°C, and the C17460 ingot is gradually rolled from 420*210mm thick to 435*17mm thick hot rolled coil.
[0074] Double-sided milling is: using double-sided milling, 0.7 mm thick material is milled from the upper and lower surfaces of the hot-rolled coil obtained after one hot rolling, and 5 mm is milled from the two side edges of the hot-rolled coil, and finally the strip size is milled to 15.6 mm thick.
[0075] The rough rolling passes are 9 times, the rolling force is controlled at 360 tons, and the bending roll force is controlled at 20 tons.
[0076] Step S4: Use a trimmer to cut off 7.5 mm on each side of the strip to remove possible cracks, burrs and other defects on the strip edge, and cut the strip to 420 mm wide. Use a 1% K616 degreasing agent to remove the surface emulsion, then use a 500-mesh diamond brush roller + a 600-mesh alumina brush roller to brush the material surface, and then perform a solid solution treatment in a hydrogen atmosphere at a temperature of 950° C. at a speed of 5 m / min.
[0077] Step S5, use 500 mesh diamond brush roller + 600 mesh alumina again to thoroughly remove the surface oxide layer generated by the initial solution treatment. Then, through three rolling passes of finishing rolling, the rolling force is controlled to 140 tons, the bending roll force is controlled to 40 tons, and the strip is further rolled to 0.7 mm strip. Under hydrogen atmosphere and 950°C, at a speed of 13m / min, a secondary solution treatment is performed.
[0078] Step S6: Repeat the use of a 500-mesh diamond brush roller + a 600-mesh alumina brush roller combination to clean and brush the surface of the C17460 strip after the secondary solution heat treatment to ensure that the surface oxide layer generated after the secondary solution treatment is completely removed. Then, after three rolling passes of finishing rolling, the rolling force is controlled to 120 tons and the bending roll force is controlled to 40 tons. Then, perform one cleaning and one straightening in sequence.
[0079] Among them, the cleaning process includes:
[0080] First, use 1% K616 degreasing agent to clean, then use 25% sulfuric acid to clean, and finally use 0.2% benzotriazole BTA passivation solution to clean, completely remove the oil and residue on the surface of the strip.
[0081] The strip is straightened once to remove residual stress. The elongation of the straightening is 0.2% and the inlet tension is 4kg / mm. 2 , the tension on the outlet side is 2.0kg / mm 2 .
[0082] Step S7, in a hydrogen atmosphere, heat the C17460 strip after drawing and straightening to 380°C at a heating rate of 120°C, and then age it for 3 hours; then heat it to 420°C, age it for another 3 hours, and then naturally cool it to 40°C before taking it out of the furnace; then perform secondary cleaning, secondary drawing and straightening, and slitting in sequence.
[0083] Among them, the secondary cleaning process includes:
[0084] First, use 1% K616 degreasing agent to clean, then use 25% sulfuric acid to clean, then use 600 mesh non-woven cloth to brush, and finally use 0.2% benzotriazole BTA passivation solution to clean.
[0085] The elongation of the secondary straightening is 0.2% and the inlet tension is 4kg / mm 2 , the tension on the outlet side is 2.5kg / mm 2 .
[0086] The composition of the C17460 beryllium copper strip of this embodiment is shown in Table 1, and its specifications, Vickers hardness, tensile strength, yield strength, elongation and conductivity are shown in Table 2.
[0087] Embodiment 2:
[0088] Step S1, in the order of electrolytic copper-nickel-electrolytic copper-zirconium-electrolytic copper, the layers are placed in a vacuum melting furnace from bottom to top, the mass ratio of electrolytic copper, nickel and zirconium is 18:1:1, and the vacuum degree is 0.074Mpa and the temperature is 1460℃, and the temperature is kept for a short time for 10min, and then refined for 38min at 1460℃, and finally the air is broken and the slag is cleared for casting. The casting process is cast through the tundish, and the straw ash is immediately covered after the transfer, and the entire liquid surface must be fully covered. Finally, after casting in a graphite mold, it is solidified at a temperature of 1070℃ for 32min to obtain a copper-nickel-zirconium alloy. Among them, the mass of each layer of electrolytic copper is the same.
[0089] Step S2, according to the mass ratio of 100:8:15:1, in the order of electrolytic copper, copper-nickel-zirconium alloy, beryllium-copper master alloy and nickel, the electrolytic copper, copper-nickel-zirconium alloy, beryllium-copper master alloy and nickel are placed in a non-vacuum melting furnace by a method of adding materials and melting at the same time, and the non-vacuum melting is carried out for 2 hours at a temperature of 1260°C, and then the casting is carried out at a temperature of 1250°C at a speed of 40mm / min, and finally, 28°C water is used to heat the furnace at a speed of 1.6m 3 / h, and water circulation cooling is carried out to obtain C17460 beryllium copper ingot.
[0090] Step S3: Using a step-by-step furnace charging method, the C17460 ingot is heated to 900° C. After being kept warm for 8 hours, hot rolling, double-sided milling and rough rolling are performed in sequence to obtain a C17460 strip with a thickness of 1.2 mm.
[0091] Among them, the rolling passes of the first hot rolling are 9 passes, the starting rolling temperature is 890°C, the hot rolling time is 13 minutes, the final rolling temperature is 680°C, and the C17460 ingot is gradually rolled from 420*210mm thick to 435*17mm thick hot rolled coil.
[0092] Double-sided milling is: using double-sided milling, 0.6mm thick material is milled from the upper and lower surfaces of the hot-rolled coil obtained after one hot rolling, and 4mm is milled from the two side edges of the hot-rolled coil, and finally the strip size is milled to 14.4mm thick.
[0093] The rough rolling has 10 passes, the rolling force is controlled at 450 tons, and the bending roll force is controlled at 30 tons.
[0094] Step S4: Use a trimmer to cut off 5 mm on each side of the strip to remove possible defects such as cracks and burrs on the strip edge, and cut the strip to 410 mm wide. Use a 2% DC-362 degreasing agent to remove the surface emulsion, then use a 500-mesh diamond brush roller + a 600-mesh nylon brush roller to brush the material surface, and then perform a solid solution treatment in a hydrogen atmosphere at a temperature of 970°C at a speed of 7m / min.
[0095] Step S5, use 500 mesh diamond brush roller + 600 mesh nylon brush again to thoroughly remove the surface oxide layer generated by the initial solution treatment. Then, through 5 rolling passes of finishing rolling, the rolling force is controlled to 170 tons, the bending roll force is controlled to 70 tons, and the strip is further rolled to 0.6 mm strip. Under hydrogen atmosphere and 970 ° C, at a speed of 10 m / min, a secondary solution treatment is carried out.
[0096] Step S6: Repeat the use of a 500-mesh diamond brush roller + a 600-mesh nylon brush roller combination to clean and brush the surface of the C17460 strip after the secondary solution heat treatment to ensure that the surface oxide layer generated after the secondary solution treatment is completely removed. After two rolling passes of finishing rolling, the rolling force is controlled to 100 tons and the bending roll force is controlled to 15 tons. Then perform one cleaning and one straightening in sequence.
[0097] Among them, the cleaning process includes:
[0098] First, use 2% DC-362 degreasing agent to clean, then use 35% nitric acid to clean, and finally use 0.3% JCDH-2 passivation solution to clean, completely remove the oil and residue on the surface of the strip.
[0099] The strip is straightened once to remove residual stress. The elongation of the straightening is 0.1% and the inlet tension is 5kg / mm. 2 , the tension on the outlet side is 2.5kg / mm 2 .
[0100] Step S7, in a hydrogen atmosphere, heat the straightened C17460 strip to 390°C at a heating rate of 130°C, and then age it for 3.5 hours; then heat it to 440°C, age it for another 3.5 hours, and then naturally cool it to 40°C before taking it out of the furnace; then perform secondary cleaning, secondary straightening and slitting in sequence.
[0101] Among them, the secondary cleaning process includes:
[0102] First, use 2% DC-362 degreasing agent to clean, then use 35% nitric acid to clean, then use 620 mesh non-woven cloth to brush, and finally use 0.3% JCDH-2 passivation solution to clean.
[0103] The elongation of the secondary straightening is 0.1% and the inlet tension is 5kg / mm 2 , the tension on the outlet side is 3.5kg / mm 2 .
[0104] The composition of the C17460 beryllium copper strip of this embodiment is shown in Table 1, and its specifications, Vickers hardness, tensile strength, yield strength, elongation and conductivity are shown in Table 2.
[0105] Embodiment 3:
[0106] Step S1, in the order of electrolytic copper-nickel-electrolytic copper-zirconium-electrolytic copper, the layers are placed in a vacuum melting furnace from bottom to top, the mass ratio of electrolytic copper, nickel and zirconium is 18:1.5:1, and the vacuum degree is 0.094Mpa and the temperature is 1530℃, and the temperature is kept for a short time for 15min, and then refined for 28min at 1530℃, and finally the air is broken and the slag is cleared for casting. The casting process is cast through the tundish, and the straw ash is immediately covered after the transfer, and the entire liquid surface must be fully covered. Finally, after casting in a graphite mold, it is solidified at a temperature of 1130℃ for 48min to obtain a copper-nickel-zirconium alloy. Among them, the mass of each layer of electrolytic copper is the same.
[0107] Step S2, according to the mass ratio of 110:10:15:1, in the order of electrolytic copper, copper-nickel-zirconium alloy, beryllium-copper master alloy and nickel, in the order of electrolytic copper, copper-nickel-zirconium alloy, beryllium-copper master alloy and nickel, in a non-vacuum melting furnace by adding materials and melting at the temperature of 1290° C. for 3 hours, then casting at the temperature of 1290° C. at a speed of 50 mm / min, finally, using 35° C. water at a speed of 1.9 m 3 / h, and water circulation cooling is carried out to obtain C17460 beryllium copper ingot.
[0108] Step S3: Using a step-by-step furnace charging method, the C17460 ingot is heated to 930° C. After being kept warm for 14 hours, hot rolling, double-sided milling and rough rolling are performed in sequence to obtain a C17460 strip with a thickness of 1.7 mm.
[0109] Among them, the rolling passes of the first hot rolling are 8 passes, the starting rolling temperature is 870°C, the hot rolling time is 10 minutes, the final rolling temperature is 660°C, and the C17460 ingot is gradually rolled from 420*210mm thick to 445*16mm thick hot rolled coil.
[0110] Double-sided milling is: using double-sided milling, 0.8mm thick material is milled from the upper and lower surfaces of the hot-rolled coil obtained after one hot rolling, and 6mm is milled from the two side edges of the hot-rolled coil, and finally the strip size is milled to 15mm thick.
[0111] The rough rolling has 8 passes, the rolling force is controlled at 280 tons, and the bending roll force is controlled at 10 tons.
[0112] Step S4: Use a trimmer to cut 6 mm from each side of the strip to remove possible cracks, burrs and other defects on the strip edge, and cut the strip to 405 mm wide. Use a 2% DC-362 degreasing agent to remove the surface emulsion, then use a 500-mesh diamond brush roller + a 600-mesh nylon brush roller to brush the material surface, and then perform a solid solution treatment in a hydrogen atmosphere at a temperature of 930° C. at a speed of 3 m / min.
[0113] Step S5, use 500 mesh diamond brush roller + 600 mesh nylon brush again to thoroughly remove the surface oxide layer generated by the initial solution treatment. Then, through three rolling passes of finishing rolling, the rolling force is controlled to 110 tons, the bending roll force is controlled to 12 tons, and the strip is further rolled to 0.6 mm strip. Under hydrogen atmosphere and 930°C, at a speed of 8m / min, a secondary solution treatment is performed.
[0114] Step S6: Repeat the use of a 500-mesh diamond brush roller + a 600-mesh nylon brush roller combination to clean and brush the surface of the C17460 strip after the secondary solution heat treatment to ensure that the surface oxide layer generated after the secondary solution treatment is completely removed. Then, after three passes of finishing rolling, the rolling force is controlled to 150 tons and the bending roll force is controlled to 60 tons. Then, perform one cleaning and one straightening in sequence.
[0115] Among them, the cleaning process includes:
[0116] First, use 1.5% DC-362 degreasing agent to clean, then use 15% nitric acid to clean, and finally use 0.1% JCDH-2 passivation solution to clean, completely remove the oil and residue on the surface of the strip.
[0117] The strip is straightened once to remove residual stress. The elongation of the straightening is 0.1% and the inlet tension is 4.5kg / mm. 2 , the tension on the outlet side is 1.8kg / mm 2 .
[0118] Step S7, in a hydrogen atmosphere, heat the straightened C17460 strip to 370°C at a heating rate of 110°C, and then age it for 2.5 hours; then heat it to 410°C, age it for another 2.5 hours, and then naturally cool it to 40°C before taking it out of the furnace; then perform secondary cleaning, secondary straightening, and slitting in sequence.
[0119] Among them, the secondary cleaning process includes:
[0120] First, use 1.5% DC-362 degreasing agent to clean, then use 15% nitric acid to clean, then use 580 mesh non-woven cloth to brush, and finally use 0.1% JCDH-2 passivation solution to clean.
[0121] The elongation of the secondary straightening is 0.1% and the inlet tension is 4.5kg / mm 2 , the tension on the outlet side is 2kg / mm 2 .
[0122] The composition of the C17460 beryllium copper strip in this embodiment is shown in Table 1. Its specifications, Vickers hardness (unit: kgf / mm 2 ), tensile strength, yield strength, elongation and conductivity are shown in Table 2.
[0123] Table 1 Chemical composition (Wt%) of C17460 beryllium copper alloy of Examples 1 to 3
[0124]
[0125] Table 2 Mechanical properties and electrical conductivity of C17460 beryllium copper alloy of Examples 1 to 3
[0126]
[0127] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. A method for improving the conductivity of C17460 beryllium copper, characterized in that: The method comprises: Step S1, in the order of electrolytic copper, nickel, electrolytic copper, zirconium and electrolytic copper, electrolytic copper, nickel and zirconium are laid from bottom to top in a vacuum melting furnace, vacuum melting for 10 to 15 minutes at a vacuum degree of 0.074 to 0.094 MPa and a temperature of 1460 to 1530° C., and then refined for 28 to 38 minutes at a temperature of 1460 to 1530° C., and then the refined alloy liquid is cast into a tundish, and then the alloy liquid surface in the tundish is covered with wood ash, and finally cast into a graphite mold and solidified to obtain a copper-nickel-zirconium alloy; In the step S1, the mass ratio of the electrolytic copper, nickel and zirconium is 17-18:1-2:1; Step S2, adding electrolytic copper, copper-nickel-zirconium alloy, beryllium-copper master alloy and nickel into a non-vacuum melting furnace for melting in the order of electrolytic copper, copper-nickel-zirconium alloy, beryllium-copper master alloy and nickel, and then casting and cooling in sequence to obtain a C17460 beryllium-copper ingot; In the step S2, the mass ratio of the electrolytic copper, the copper-nickel-zirconium alloy, the beryllium-copper master alloy and nickel is 100-110:8-10:14-15:1; Step S3, using a walking beam furnace to heat the C17460 ingot to 900-930° C., keeping the temperature for 8-14 hours, and then performing hot rolling, double-sided milling and rough rolling in sequence to obtain a C17460 strip with a thickness of 1.2-1.7 mm; Step S4, after trimming and cleaning and brushing the C17460 strip in sequence, a solid solution treatment is performed in a hydrogen atmosphere at a temperature of 930 to 970° C. at a speed of 3 to 7 m / min; Step S5, after the C17460 strip after the first solution heat treatment is subjected to second cleaning and brushing and first finish rolling in sequence, a second solution treatment is performed in a hydrogen atmosphere at a temperature of 930 to 970° C. at a speed of 8 to 13 m / min; Step S6, sequentially performing three cleaning and brushing, two finishing rolling, one cleaning and one straightening on the C17460 strip after the secondary solution heat treatment; Step S7, in a hydrogen atmosphere, heat the C17460 strip after the primary straightening to 370-390°C at a heating rate of 110-130°C, and then age it for 2.5-3.5 hours; then heat it to 410-440°C, age it for another 2.5-3.5 hours, and then naturally cool it to 40°C before taking it out of the furnace; then perform secondary cleaning, secondary straightening and slitting in sequence.
2. The method according to claim 1, characterized in that In the step S1, the mass of each layer of electrolytic copper laid in the order of electrolytic copper, nickel, electrolytic copper, zirconium and electrolytic copper is the same; In the step S1, the solidification temperature is 1070-1130° C. and the solidification time is 32-48 minutes.
3. The method according to claim 2, characterized in that In the step S2, the beryllium content in the beryllium copper master alloy is 3.2-3.8%, and the rest is copper; In step S2, the smelting temperature is 1260-1290°C and the time is 2-3h; In step S2, the casting temperature is 1250-1290°C, the speed is 40-50 mm / min; the cooling medium is water at 28-35°C, and the water circulation speed is 1.6-1.9 m / min. 3 / h.
4. The method according to claim 3, characterized in that In step S3, the hot rolling has 8 to 10 passes, the start rolling temperature is 870 to 890° C., the hot rolling time is 10 to 13 minutes, and the final rolling temperature is 660 to 680° C.; In step S3, the double-sided milling is: milling 0.6-0.8 mm thick material from the upper surface and the lower surface of the hot-rolled coil obtained after the first hot rolling, and milling 4-6 mm wide material from the two sides of the hot-rolled coil; In the step S3, the rough rolling is performed in 8 to 10 passes, the rolling force is controlled to be 280 to 450 tons, and the bending roll force is controlled to be 10 to 30 tons.
5. The method according to any one of claims 1 to 4, characterized in that: In the step S5, the number of rolling passes of the primary finishing rolling is 3 to 5, the rolling force is controlled to be 110 to 170 tons, and the bending roll force is controlled to be 12 to 70 tons.
6. The method according to claim 5, characterized in that In step S6, the secondary finishing rolling has 2 to 3 passes, the rolling force is controlled to be 100 to 150 tons, and the bending roll force is controlled to be 15 to 60 tons; In step S6, the elongation of the first straightening is 0.1-0.2%, and the inlet tension is 4-5 kg / mm 2 , the tension on the outlet side is 1.8~2.5kg / mm 2 .
7. The method according to claim 6, characterized in that In step S6, the one-time cleaning process includes: First use 1-2% degreasing agent for cleaning, then use 15-35% acid solution for cleaning, and finally use 0.1-0.3% passivation solution for cleaning; In step S7, the secondary cleaning process includes: First, use 1-2% degreasing agent for cleaning, then use 15-35% acid solution for cleaning; then use 580-620 mesh non-woven cloth for brushing; finally use 0.1-0.3% passivation solution for cleaning.
8. The method according to claim 7, characterized in that The degreasing agent is K616 or DC-362 degreasing agent; The acid solution is sulfuric acid or nitric acid; The passivation solution is benzotriazole BTA or JCDH-2.
9. The method according to claim 8, characterized in that In step S7, the elongation of the secondary straightening is 0.1-0.2%, and the inlet tension is 4-5 kg / mm 2 , the tension on the outlet side is 2~3.5kg / mm 2 .
Citation Information
Cited By
Regulation and control method for synergistically improving strong-electrical property of elastic copper alloy
CN121610666A